Peningkatan Konsistensi Publikasi Konten Media Sosial Melalui Sistem Penjadwalan Digital Sebagai Strategi Efisiensi Pengelolaan Konten - Sabrina, Zahra Naswa; Fitriyah, Zumrotul (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2026)
Consistency in content publication is one of the main challenges in social media management, particularly for business-to-business (B2B) service organizations that rely on educational content as a communication and branding tool. The absence of a structured scheduling system often leads to irregular posting, uneven workload distribution, and difficulties in monitoring content production progress. This activity aims to improve the consistency of social media content publication through the implementation of a digital scheduling system as a strategy to enhance content management efficiency. The method used is participatory observation with a descriptive qualitative approach, in which the author was directly involved in the content planning, production, and scheduling processes during an internship program. The implementation of the digital scheduling system utilized a content calendar and task management platform to organize the content workflow systematically. The results indicate an improvement in publication consistency, a more organized workflow, and a more stable growth of social media followers. The digital scheduling system supports efficient content management without involving sensitive company data. These findings are expected to serve as a practical reference for organizations or MSMEs in managing social media content sustainably